A single point mutation in the Bemisia tabaci cytochrome-P450 CYP6CM1 causes enhanced resistance to neonicotinoids. (May 2023) - Pym, Adam; Mina, John G.M.; Troczka, Bartlomiej J.; Hayward, Angela; Daum, Eve; Elias, Jan; Slater, Russell; Vontas, John; Bass, Chris; Zimmer, Christoph T.
Abstract: The tobacco whitefly, Bemisia tabaci, is a polyphagous crop pest which causes high levels of economic damage across the globe. Insecticides are often required for the effective control of this species, among which the neonicotinoid class have been particularly widely used. Deciphering the mechanisms responsible for resistance to these chemicals is therefore critical to maintain control of B. tabaci and limit the damage it causes. An important mechanism of resistance to neonicotinoids in B. tabaci is the overexpression of the cytochrome P450 gene CYP6CM1 which leads to the enhanced detoxification of several neonicotinoids. In this study we show that qualitative changes in this P450 dramatically alter its metabolic capacity to detoxify neonicotinoids. CYP6CM1 was significantly over-expressed in two strains of B. tabaci which displayed differing levels of resistance to the neonicotinoids imidacloprid and thiamethoxam. Sequencing of the CYP6CM1 coding sequence from these strains revealed four different alleles encoding isoforms carrying several amino acid changes. Expression of these alleles in vitro and in vivo provided compelling evidence that a mutation (A387G), present in two of the CYP6CM1 alleles, results in enhanced resistance to several neonicotinoids. These data demonstrate the importance of both qualitative and quantitative changes in genes encoding detoxification enzymes in the evolution of insecticide resistance and have applied implications for resistance monitoring programs. Graphical abstract: Image 1 Highlights: Four different alleles of the P450 CYP6CM1 were linked to resistance to neonicotinoids. Drosophila melanogaster and insect cell line expression revealed allelic associated differences in metabolic capacity. Further analysis revealed that the mutation A387G was responsible for the enhanced resistance to several neonicotinoids.